Trans fatty acids in the Portuguese food market - Costa, N (2016)
Consistent evidence exist on the harmful health effects of industrial trans fatty acids (TFA). In order to have accurate data on TFA intake and implement adequate measures to reduce their intake, each country should have updated estimates of TFA content in the diet. The objective of the present study was to provide data on the TFA content in food commercialized in the Portuguese market. The results on the TFA content of 268 samples acquired between October and December 2013 are reported. Samples were categorized as margarines and shortenings (n = 16), spreadable chocolate fats (n = 6), fried potatoes and chips (n = 25), industrial bakery (n = 4), breakfast cereals (n = 3), pastry products (n = 120), seasonings (n = 5), instant soups (n = 5), instant desserts (n = 6), chocolate snacks (n = 4), microwave popcorn (n = 4), cookies, biscuits and wafers (n = 53), and fast-food (n = 13), with butter (n = 4) included for comparison purposes. TFA were quantified by gas chromatography. Total TFA content in the fat ranged from 0.06% to 30.2% (average 1.9%), with the highest average values in the "biscuits, wafers and cookies" group (3.4% TFA), followed by the pastry group (2.0%). Fifty samples (19%) had TFA superior to 2% in the fat. These findings highlight there is still much need for improvement in terms of the TFA content in Portuguese foods, particularly in traditional pastry. (C) 2015 Published by Elsevier Ltd.